Hybrid Mathieu Urethroplasty vs. Tubularized Incised Plate Urethroplasty for the Management of Distal Penile Hypospadias With a Small Glans - Kurdi, Mazen Omar; Eldessouki, Nagi Ibrahim; Khirallah, Mohammad Gharieb (Frontiers in Pediatrics, 2022)
introduction: Distal hypospadias is a common anomaly. Different surgical techniques have evolved through the years to manage this anomaly. Several factors may affect the prognosis. One of them is glans size. We compared the hybrid Mathieu urethroplasty (HMU)and the tubularized incised plate urethroplasty (TIPU) for the management of distal hypospadias with a small glans. Methods: Sixty-eight patients with distal hypospadias were included and categorized into two groups. Group A (n= 33) and group B (n= 35) patients were treated by HMU and TIPU, respectively. All patients had a small glans. In group A, the patients underwent Mathieu urethroplasty plus a deep incision of the urethral plate. In group B, the patients underwent TIPU. Urethral stents were used in all cases. Hypospadias objective score evaluation (HOSE) was used to assess the results. Results: Urethrocutaneous fistulae developed in 2 cases in group A and 6 cases in group B. Meatal stenosis was significantly lower (one case in group A vs 8 cases in group B). Glanular dehiscence occurred in 2 cases in group A and 5 cases in group B. The small glans strongly correlated with the development of both urethrocutaneous fistulae and meatal stenosis where the odd ratios were 3.500 (1.383 –7.879) and 9.481 (1.114 – 12.669), respectively. Conclusion: both techniques showed efficacy during management of patients with a small glans. HMU had better outcomes, shorter duration of stent and lesser incidence of complications than TIPU. Small glans was significantly related to urethrocutaneous fistulae and meatal stenosis in group B.